2015
DOI: 10.1111/jipb.12338
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, structure and biosynthetic gene families of (1,3;1,4)‐β‐glucan in Sorghum bicolor

Abstract: In cereals, the presence of soluble polysaccharides including (1,3;1,4)-b-glucan has downstream implications for human health, animal feed and biofuel applications. Sorghum bicolor (L.) Moench is a versatile crop, but there are limited reports regarding the content of such soluble polysaccharides. Here, the amount of (1,3;1,4)-b-glucan present in sorghum tissues was measured using a Megazyme assay. Very low amounts were present in the grain, ranging from 0.16%-0.27% (w/w), while there was a greater quantity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 76 publications
3
38
0
Order By: Relevance
“…Eukaryotic CesA genes were first cloned from cotton (Pear et al, 1996) and have been later reported from Arabidopsis (10), maize (12), poplar (18), and 14 in foxtail millet (Richmond and Somerville, 2000; Appenzeller et al, 2004; Djerbi et al, 2005; Muthamilarasan et al, 2015). Cluster analysis of CESA proteins found to be clustered with CSLD and CSLF proteins (Figure 2) consistent with earlier reports (Ermawar et al, 2015a). The clustering is due the presence of common conserved domains among cellulose synthase and cellulose synthase like family of proteins.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Eukaryotic CesA genes were first cloned from cotton (Pear et al, 1996) and have been later reported from Arabidopsis (10), maize (12), poplar (18), and 14 in foxtail millet (Richmond and Somerville, 2000; Appenzeller et al, 2004; Djerbi et al, 2005; Muthamilarasan et al, 2015). Cluster analysis of CESA proteins found to be clustered with CSLD and CSLF proteins (Figure 2) consistent with earlier reports (Ermawar et al, 2015a). The clustering is due the presence of common conserved domains among cellulose synthase and cellulose synthase like family of proteins.…”
Section: Resultssupporting
confidence: 91%
“…In the present investigation, the large family of sorghum Csls has been classified into 8 different groups (CslA to H) based on the phylogenetic studies (Ermawar et al, 2015a; Figure 2). Particularly, two clusters, CslF and CslH were observed be unique to sorghum with no Arabidopsis homologs, which is in agreement with the previous reports of these clusters as grass specific (Paterson et al, 2009; Ermawar et al, 2015a) while no sorghum Csl genes were clustered in Clusters CslB and CslG (Figure 2). Similar clustering of SbCsl genes has been reported previously in the sorghum draft genome report (Paterson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After hydrolysis with lichenase (EC 3.2.1.73; 1,3‐1,4‐beta‐D‐glucan 4‐glucanohydrolase), a portion of the hydrolysate was collected and stored at −20°C for high pH anion exchange chromatography (HPAEC) analysis of the G4G3G (DP3) and G4G4G3G (DP4) oligosaccharides. Hydrolysates were separated on a solid phase extraction (SPE) cartridge packed with graphitized carbon (Varian Bond Elute Carbon 50mg‐1), as outlined in Ermawar et al (). The oligosaccharides were dissolved in 1 mL water and analyzed using HPAEC on a Dionex ICS‐5000 using a DionexCarboPAC PA‐200 column (3 × 250 mm), as outlined by Ermawar et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The DP3:DP4 ratio was determined by High-Performance Anion-Exchange Chromatography (HPAEC) as described in Ermawar et al (2015). Lichenase enzyme (Megazyme Int., Wicklow, Ireland) was used to release oligosaccharides for profiling by HPAEC.…”
Section: Dp3:dp4 Analysismentioning
confidence: 99%